2010
DOI: 10.1186/1471-2334-10-4
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of human Toxoplasma gondii infection in China

Abstract: BackgroundToxoplasmosis is an important zoonotic parasitic disease worldwide. In immune competent individuals, Toxoplasma gondii preferentially infects tissues of central nervous systems, which might be an adding factor of certain psychiatric disorders. Congenital transmission of T. gondii during pregnancy has been regarded as a risk factor for the health of newborn infants. While in immune-compromised individuals, the parasite can cause life-threatening infections. This study aims to investigate the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
71
5
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 22 publications
(30 reference statements)
17
71
5
3
Order By: Relevance
“…The comparison of the seropositivity of the pregnant women in Divinópolis with the prevalence of toxoplasmosis in other countries showed that the number of cases found in this study is twice that diagnosed in the Palestine (27.9%) 6 , 4 times higher than in China (12.3%) 2 , and also higher than in Venezuela (33%) 1 . In contrast, the numbers found were similar to the prevalence found in rural populations of France (47%) 4 , Albania (48.6%) 5 , and rural (57.6%) and urban (46.5%) areas of Egypt 6 .…”
Section: Discussionmentioning
confidence: 86%
“…The comparison of the seropositivity of the pregnant women in Divinópolis with the prevalence of toxoplasmosis in other countries showed that the number of cases found in this study is twice that diagnosed in the Palestine (27.9%) 6 , 4 times higher than in China (12.3%) 2 , and also higher than in Venezuela (33%) 1 . In contrast, the numbers found were similar to the prevalence found in rural populations of France (47%) 4 , Albania (48.6%) 5 , and rural (57.6%) and urban (46.5%) areas of Egypt 6 .…”
Section: Discussionmentioning
confidence: 86%
“…The seroprevalence of T. gondii among pregnant women in Africa ranges from 25 to 92.5 % (Torgerson and Mastroiacovo 2013), which is very high compared to the seroprevalence in Arab countries and much higher compared to the U.K. (6-17 %), France (50-60 %), North America (10-25 %), and Asia (10-60 %), but comparable to countries in South America (45-80 %) (Al-Nakib et al 1983, Jones et al 2007Dromigny et al 1996;Pal et al 1996;Baril et al 1999;Nash et al 2005;Dubey and Jones 2008;Rosso et al 2008;Fernandes et al 2009;Sroka et al 2010;Xiao et al 2010). Worldwide, about 1,90,100 cases of congenital toxoplasmosis are reported every year.…”
Section: Discussionmentioning
confidence: 99%
“…T. gondii cause Toxoplasmosis which is an important zoonotic disease and responsible for major economic losses in all classes of livestock through abortion, stillbirth and neonatal losses [8,[9][10].Approximately one-third of the human world's population is infected by T. gondii [11,7].…”
Section: Introductionmentioning
confidence: 99%